LIPASE INHIBITORS FROM NIGELLA SATIVA AND PUNICA GRANATUM AS AN EFFECTIVE APPROACH TOWARDS CONTROLLING OBESITY - Shamsiya, Trichur Khabeer; J R, Manjunatha; H K, Manonmani (LIFE: International Journal of Health and Life-Sciences, 2016)
Two distinct lipase inhibitor cocktails RAYstat4ns and SHAMstat3pg have been purified from seeds of Nigella sativa and Punica granatum respectively. Structural characterization has shown RAYstat4ns to be a mixture of 3 polyunsaturated fatty acids and one saturated fatty acid while SHAMstat3pg is a triglyceride mixture comprising of three different kinds of polyunsaturated fatty acids. Ethanol extracted fractions of seeds of Nigella saliva and Punic a granatum having high lipase inhibitory activity were purified by HPLC followed by TLC to yield respectively RAYstat4ns and SHAMstat3pg . These plant based lipase inhibitors have shown good lipase inhibitory activity against pancreatic lipase with mixed type of inhibition. RAYstat4ns and SHAMstat3pg have also shown inhibition of hormone sensitive lipase. The experimental IC50 of the purified lipase inhibitors RAYstat4ns and SHAMstat3pg was found to be respectively 4.02μg/μl and 7.35 μg/μl for pancreatic lipase and 6.31 μg/μl and 11.45 μg/μl respectively for hormone sensitive lipase. Hence ,these plant-based lipase inhibitors can be used in controlling lipolysis and insulin resistance in addition to inhibiting absorption of dietary lipid into the living system. In vivo studies could help confirm the potency of these plant based isolates as efficient lipase inhibitors.